2008
DOI: 10.2105/ajph.2007.123471
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of Skilled Birth Attendant Utilization in Afghanistan: A Cross-Sectional Study

Abstract: Objectives. We sought to identify characteristics associated with use of skilled birth attendants where health services exist in Afghanistan. Methods. We conducted a cross-sectional study in all 33 provinces in 2004, yielding data from 617 health facilities and 9917 women who lived near the facilities and had given birth in the past 2 years. Results. Only 13% of respondents had used skilled birth attendants. Women from the wealthiest quintile (vs the poorest quintile) had higher odds of use (odds ratio [OR] … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

24
83
5

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 99 publications
(112 citation statements)
references
References 16 publications
24
83
5
Order By: Relevance
“…10 Mayhew et al found that wealth was the strongest determinant of skilled birth attendant use. 16 Women in the poorest quantile had lower odds of skilled birth attendant use compared to women in each of the other quintiles; the strength of the association increased with each wealth quintile. 16 While the health system is designed to accomodate the low income population, even a small fee for health care or drugs can prevent the low income population segment from accessing health care specialists.…”
Section: Sociocultural Practicesmentioning
confidence: 89%
See 4 more Smart Citations
“…10 Mayhew et al found that wealth was the strongest determinant of skilled birth attendant use. 16 Women in the poorest quantile had lower odds of skilled birth attendant use compared to women in each of the other quintiles; the strength of the association increased with each wealth quintile. 16 While the health system is designed to accomodate the low income population, even a small fee for health care or drugs can prevent the low income population segment from accessing health care specialists.…”
Section: Sociocultural Practicesmentioning
confidence: 89%
“…13 Lack of human and technical resources were the major reported reasons associated with adverse maternal and infant health outcomes in the poor-resource setting of Afghanistan. [14][15][16] The findings of the studies conducted between 2001 and 2011 that there is a need to improve health facilities, and to increase the number of professionals in both urban and rural areas in order to improve maternal health. [17][18][19][20][21][22][23][24][25][26] Published research suggests that the provision of expanded health services alone would not lead to the increased utilization of Bartlett et al found that 93% of women who died due to maternity-related causes were illiterate.…”
Section: Health Carementioning
confidence: 99%
See 3 more Smart Citations